Effect of preconditioning induced by acupoint tens on IMA and UII level of rowing athletes - Yang, Y.; Li, Z.; Liu, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Being one of the main therapies of Traditional Chinese Medicine, acupuncture is advantageous for its safety, efficiency, convenience and low price. With regard to the feasibility of acupuncture in exercise training, non-traumatic preconditioning induced by acupoint transcutaneus electrical nerve stimulation (TENS) was applied in this study. The aim was to observe its function on heart protection, so as to offer experimental data for future applications.